Treatment of displaced intraarticular calcaneal fractures with or without bone grafts: A systematic review of the literature - Yang, Yunfeng (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: The necessity of bone grafts in the treatment of intraarticular calcaneal fractures continues to be one of the most debated topics in foot and ankle surgery. The purpose of this study was to determine whether there are sufficient objective cumulative data in the literature to compare the two methods and if the bone graft was needed in surgical treatment of intraarticular calcaneal fractures. MATERIALS AND METHODS: A comprehensive search of all relevant articles from 1990 to 2010 was conducted. Two reviewers evaluated each study to determine its suitability for inclusion and collected the data of interest. Meta-analytic pooling of group results across studies was performed for the two treatment methods. RESULTS: The systematic review identified 32 primary studies with 1281 fractures, which contained 4 comparative studies, 13 with bone grafts, and 15 without bone grafts in treatment methods. The infection rate in bone graft group was higher through statistically insignificant than in non-graft group (8.3% vs. 6.3%) No significant difference was found between good reduction rate, postoperative osteoarthritis rate, and subtalar fusion rate. The average full weight-bearing time in bone graft group was significantly lower (5.4 months) than in non-graft group (10.5 months). The mean postoperative Böhler's angle was significantly higher in bone graft group (lose due to collapse was significancy less). For the efficacy outcomes, the bone graft group had a lower American Orthopaedic Foot and Ankle Society Score (AOFAS) (71.4 points vs. 80.5 points) but a higher Creighton score (89.9 points vs. 81.0 points) compared with non-graft group. Pooled mean results showed 35% of the patients in bone graft group had an excellent result, 40% had a good result, 21% had a fair result, and 4% had a poor result. In the non-graft group, the corresponding values were 34, 42, 14, and 10%, respectively. CONCLUSIONS: The operative treatment of intraarticular calcaneal fractures with bone grafts could restore the Böhler's angle better and the patients could return to full weight bearing earlier. However, the functional and efficacy outcomes appear to be similar between the two treatment groups. There were more joint depression and comminuted fractures in the bone graft group, and the mean followup time was shorter. Large sample comparative studies are still needed.